Lipid profile in patients with fibromyalgia and myofascial pain syndromes - Ozgocmen, S; Ardicoglu, O (Yonsei Univ Coll Medicine, 2000)
In this study serum lipid profile of patients with fibromyalgia syndrome (FMS) and myofascial pain syndrome (MPS) were investigated and compared with healthy controls. Thirty women who had FMS and 12 women who had MPS with the characteristic trigger points (TrP), especially on the periscapular region were included in this study. Thirty one age matched healthy women were assigned as a control group. All of the subjects were sedentary healthy housewives. Total cholesterol, triglyceride and high-density lipoprotein cholesterol (HDL-c) levels were not significantly different between the FMS and control groups. On the other hand the MPS group had total cholesterol (198.7 vs 172.9 mg/dL, p=0.003), triglyceride (124.7 vs 87.6 mg/dL, p=0.01), low-density lipoprotein cholesterol (LDL-c) (127.5 vs 108.4 mg/dL, p=0.02) and very low-density lipoprotein cholesterol (VLDL-c) (24.9 vs 17.3 mg/dL, p=0.008) levels, which were significantly higher than the controls. There was no significant difference between the lipid profiles in the FMS and MPS groups. Tissue compliance, which was measured from trigger points in the MPS group, correlated significant ly with total cholesterol and LDL-e levels. In conclusion, a significant difference was found between the lipid levels of patients with MPS and the controls. More extensive investigation of lipid and lipoprotein levels is required to determine whether high lipid levels are the cause or result of MPS.
Keywords: fibromyalgia; myofascial pain; lipid profile; cholesterol